Season's Greetings to all our readers!

\[y = \frac{\log_e\left(\frac{x}{m}-sa\right)}{r^2}\]

\[\Rightarrow yr^2 = \log_e\left(\frac{x}{m}-sa\right)\]

\[\Rightarrow e^{yr^2} = \frac{x}{m}-sa\]

\[\Rightarrow me^{yr^2} = x-msa\]

\[\Rightarrow me^{rry} = x-mas\]

 

Comments

David Shaffer
(Jan 6, 2017)
love the nerdy humour

yp^2 * new = (log(ear)+log(y))/log(ha)

captcha

Find by key-word


RECENT POSTS

In Richards (2012) I compared seventeen different parametric models for ... Read more
If you read almost any paper on modelling mortality you ... Read more
The analysis of cohort effects has long fascinated the actuarial ... Read more
Stephen Richards
Stephen Richards is the Managing Director of Longevitas